Public health implications of the send-down movement: long-term effects on cognitive ability of rural older adults in China - Guangchuan Zhao; Guangchuan Zhao; Guangchuan Zhao; Chen Su (Frontiers in Public Health)
ObjectiveThis study examines the long-term effects of the send-down movement on the cognitive ability of rural older adults in China, focusing on how early-life exposure to human capital interventions shapes late-life cognitive trajectories.MethodsLeveraging four waves of the China Health and Retirement Longitudinal Study (CHARLS, 2011–2018), we employ a cohort difference-in-differences (cohort DID) design to compare cognitive outcomes between rural residents exposed to send-down youths (SDYs) during childhood and non-exposed cohorts. Mechanisms are analyzed through a multi-mediation framework integrating educational attainment, non-agricultural work, social engagement, and fertility behaviors.ResultsThe analysis demonstrates that exposure to SDYs significantly enhanced cognitive ability among rural older adults, resulting in a 0.857-point increase in cognitive ability score, a 4.33 percentage-point reduction in cognitive decline, and a 6.76 percentage-point decrease in cognitive impairment incidence. Mechanism analysis reveals that exposure to SDYs primarily influenced late-life cognitive ability through four pathways: improving rural children's educational attainment, increasing their probability of obtaining non-agricultural work, enhancing social engagement, and reducing fertility rates.ConclusionThe send-down movement positively influenced the cognitive health of rural older adults, underscoring the enduring impact of childhood access to educational resources on cognitive ability throughout the life course. Policy initiatives integrating early-life education with adult opportunity structures could yield compounded cognitive dividends, particularly in resource-limited rural settings.